The Influence Of Consumers’ Online Brand-Related Activities (Cobra) On Customers’ Green Brand Awareness: An Empirical Case Study In Solo Raya Region, Indonesia - Ebida Zakiya; Kussudyarsana; Imronudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aimed to analyze the influence of Consumers’ Online Brand-Related Activities (COBRA), which included consuming, contributing, and creating, on green brand awareness of environmentally friendly cosmetic products of The Body Shop in the Solo Raya region. This research employed a quantitative approach. Primary data were collected by distributing questionnaires to 220 respondents selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 29. The findings revealed that, partially, consuming, contributing, and creating behaviors had a positive and significant effect on green brand awareness. Simultaneously, the three dimensions of COBRA also demonstrated a significant influence on green brand awareness. These results indicated that the higher the level of consumer engagement in online brand-related activities, both actively and passively, the higher the level of consumer awareness toward green brand. This study provided practical implications for companies in formulating effective digital marketing strategies to enhance green brand awareness through social media platforms.